Sintomatologia depressiva em residentes em instituições de longa permanência públicas ou beneficentes de Belo Horizonte, Minas gerais, Brasil - Leonardo Freitas e Silva (2012)
Introduction: The aging population increases the demand for long-term care homes for the elderly (LTC's). In Brazil, neuropsychiatric disorders in elders are mentioned as risk factors for institutionalization and are still poorly studied. Objective: To investigate the prevalence and factors associated with depressive symptoms among elderly in public or beneficent LTCs in Belo Horizonte. Methodology: Cross-sectional study with elderly (60 + years) of five LTC's in the city, with at least 50 residents of both sexes. The following items were investigated by questionnaire and medical records: sex, age, education, lifestyle, chronic diseases and medication use. The Mini Mental State Examination Score was used for cognitive assessment. Depressive symptoms were measured by the Geriatric Depression Scale. Assessments of activities of daily living (ADLs) instrumental and basic were measured by Pfeffer and Katz indexes, respectively. The data were inserted into Epi-Info and analyzed in STATA 10. Project approved by the COEP-UFMG. Results: Of 378 residents, only 209 (55.3%) were able to complete the questionnaire and the scales. Of this total, 126 (60.3%) were women and 83 (39.7%) were men, with an average age of 75.9 ± 8.9 years. Depressive symptomatology was found in 34.0% of residents, cognitive deficits in 49.7%, dependence for instrumental ADL's in 82.3% and dependence for basic ADLs in 35.8%. The lower educational level was associated with dependence for instrumental ADLs, and physical inactivity was associated with depressive symptoms and functional dependence. Two hundred (95.6%) elders had some disease: 142 (67.9%) had high blood pressure, 39 (18.7%) diabetes, 42 (20.1%) with a history of cerebrovascular accident, 23 (11.0%) with dementia, 55 (26.3%) depressive disorder, 18 (8.6%) psychotic behavior and two (0.96%) bipolar disorder. A large proportion of elderly people were taking medication for psychiatric disorders: 94 (45.0%) were using antidepressants, 62 (29.7%) antipsychotics, 37 (17.7%) benzodiazepines and 11 (5.3%) mood stabilizers. Conclusion: Particular attention is drawn to the high percentage of depressive symptoms, cognitive impairment and functional dependency, as well as the use of psychiatric medication among residents of LTC's public or beneficent in Belo Horizonte, especially considering that 45% of this group was already unable to participate in the study.